P185 Patient perceptions of physical activity following a diagnosis of giant cell arteritis: a multinational qualitative study. (20th April 2020) - Austin, Keziah; Dures, Emma; Almeida, Celia; Cramp, Fiona; Gilbert, Kate; Guly, Catherine; Hill, Catherine; Mackie, Sarah; O'Brien, Anne; Watts, Richard; Robson, Joanna
Abstract: Background: Giant cell arteritis (GCA) is the most common vasculitis in the UK, with an incidence of 220 cases per million in adults over 50 years of age. The physical symptoms as well as the side effects of glucocorticoids may impact patients' ability to exercise. Maintaining physical activity (PA) has been shown to be beneficial to disease activity in other inflammatory conditions and is also a specific priority for GCA patients. The aim of this project was to explore patient perceptions of physical activity in GCA. Methods: Multinational qualitative study, using interviews with 36 patients from the UK (25) and Australia (11), all of whom had a definitive diagnosis from imaging or biopsy. Interviews were recorded, transcribed, and analysed using inductive thematic analysis. This is secondary analysis of data collected to explore health-related quality of life in people with GCA. Results: 107 individual themes were reported by patients, which divided broadly into two overarching themes: barriers to (59) and facilitators of (48) physical activity. Four sub-themes were identified within each overarching theme. For barriers, these were: negative physical symptoms (including effects of disease flares, visual loss, fatigue, weakness, pain and stiffness), lack of physical capability (including poor stamina, confidence and mobility), negative perceptions around PA, and negative reinforcement (i.e. new physical symptoms following PA). Facilitators of physical activity were also grouped into four sub-themes: external facilitators (including motivation from healthcare professionals), access to appropriate facilities, personal strategies (including pacing and goal-setting) and personal facilitators (including internal motivation to improve symptoms, and positive reinforcement from noticing physical and psychological benefits of PA). Conclusion: There are a variety of barriers to physical activity in GCA patients, including patients being fearful of exercise. In other inflammatory conditions, patients report improved symptoms following physical activity as well as wider benefits to general wellbeing and cardiovascular health. Education, motivational interviewing, and personalised strategies may be beneficial components of an intervention to support physical activity in patients with GCA. Disclosures: K. Austin None. E. Dures Grants/research support; Has previously received an independent learning grant from Pfizer, however the work has been completed and the grant has been closed. C. Almeida None. F. Cramp None. K. Gilbert None. C. Guly None. C. Hill None. S. Mackie None. A. O'Brien None. R. Watts None. J. Robson None.